2016
DOI: 10.1089/acm.2015.0350
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of HIV/AIDS Patients with Qi-Yin Deficiency and Dampness-Heat Retention

Abstract: Objectives: Traditional Chinese Medicine (TCM) applied in the clinic as a complementary and alternative therapy has helped improve immunity and reduce side effects and symptomatic treatment in patients with HIV/AIDS. However, the mechanisms of TCM syndromes are not clear. Transcriptomics enables the study of such TCM syndromes.Design: This study compared the messenger RNA (mRNA) expressions of healthy persons and patients with HIV/AIDS who had two common TCM syndromes, qi-yin deficiency and dampness-heat reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the previous study, we screened serum protein profiles in the rat model of YDH syndrome by using iTRAQ coupled with 2DLC‐MS/MS and validated the protein levels by ELISA. Three proteins were found to be potential biomarkers that may be related to the regulation of cytokines, chemokines release, oxidative stress, and lipolysis in YDH syndrome (Liu, Chen, et al, 2016; Liu, Mao, et al, 2016). Furthermore, YDH syndrome‐treated rats by nourishing Yin and decreasing internal heat were also explored, and it was found that several proteins linked to the immune response, coagulation and complement cascades were altered by the treatment (Liu et al, 2018).…”
Section: Proteomics Research On Tcm Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study, we screened serum protein profiles in the rat model of YDH syndrome by using iTRAQ coupled with 2DLC‐MS/MS and validated the protein levels by ELISA. Three proteins were found to be potential biomarkers that may be related to the regulation of cytokines, chemokines release, oxidative stress, and lipolysis in YDH syndrome (Liu, Chen, et al, 2016; Liu, Mao, et al, 2016). Furthermore, YDH syndrome‐treated rats by nourishing Yin and decreasing internal heat were also explored, and it was found that several proteins linked to the immune response, coagulation and complement cascades were altered by the treatment (Liu et al, 2018).…”
Section: Proteomics Research On Tcm Syndromesmentioning
confidence: 99%
“…A series of inflammatory and immune‐related genes were identified, and the target gene IL‐8 was shown to be linked to the pathology of coronary artery disease patients (Ma et al, 2009). The mRNA expression in Qi‐Yin‐deficiency syndrome and dampness‐heat retention syndrome of patients with HIV/AIDS has also been explored, and TCM syndromes were changed with the change in gene expression (Liu, Chen, et al, 2016; Liu, Mao, et al, 2016).…”
Section: Transcriptomics Research Of Tcm Syndromesmentioning
confidence: 99%